Carbon Nanotube Network Embroidered Graphene Films for Monolithic All‐Carbon Electronics. (18th November 2014) - Shi, Enzheng; Li, Hongbian; Yang, Long; Hou, Junfeng; Li, Yuanchang; Li, Li; Cao, Anyuan; Fang, Ying
<x xml:space="preserve">Abstract</x> A unique cage growth of graphene is developed by using carbon nanotube (CNT) spider webs as porous templates, resulting in CNT/graphene hybrids with high conductivity and mechanical flexibility. Furthermore, monolithic all‐carbon transistors with graphene as active elements and CNT/graphene hybrids as contacts and interconnects are directly formed by chemical synthesis, and flexible all‐carbon bioelectronics are subsequently demonstrated for in vivo mapping of cardiac signals. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>